Exploring Environmental Factors Contributing to Fluid Loss in Diapers Placed in Neonatal Incubators. (3rd April 2023) - Jones-Hepler, Bonnie; Silva, Susan; Elmore, Kristen; Vance, Ashlee; Harney, Jane; Brandon, Debra
Abstract : Purpose: Assessing fluid output for infants in the neonatal intensive care unit is essential to understanding fluid and electrolyte balance. Wet diaper weights are used as standard practice to quantify fluid output; yet, diaper changes are intrusive and physiologically distressing. Less frequent diaper changes may have physiologic benefits but could alter diaper weights following extended intervals. Methods: This pilot study examined the impact of initial diaper fluid volume, incubator air temperature and humidity, and diaper brand on wet diaper weight over time. Baseline fluid volume was instilled, and then diapers were placed in a neonatal incubator. Wet diaper weight was assessed longitudinally to determine changes in fluid volume over time. A factorial design with repeated measures (baseline, 3 hours, and 6 hours) was used to explore the effects of diaper brand (brand 1 vs brand 2), baseline fluid volume (3 mL vs 5 mL), and incubator temperature (28°C vs 36°C) and humidity (40% vs 80%) on the trajectory of weight in 80 diapers. Results: Wet diaper weight was significantly reduced over 6 hours ( P < .005). However, wet diaper weight increased in 80% humidity, but decreased in the 40% humidity over time ( P < .0001). Baseline fluid volume, incubator temperature, and diaper brand did not influence wet diaper weight over time (all P > .05). Implications: Understanding environmental factors that influence the trajectory of wet diaper weight may support clinicians in optimizing the interval for neonatal diaper changes to balance the impact of intrusive care with need to understand fluid volume loss.